Clinico-hematological profile of Chediak-Higashi syndrome: Experience from a tertiary care center in south India - Arun Roy (Indian Journal of Pathology and Microbiology, 2011)
Introduction: Chediak-Higashi syndrome (CHS) is a rare autosomal recessive disorder characterized by partial ocular and cutaneous albinism, increased susceptibility to pyogenic infections, the presence of large lysosomal-like organelles in most granule-containing cells and a bleeding tendency. The abnormal granules are most readily seen in blood and marrow leukocytes, especially granulocytes; and in melanocytes. Other clinical features include silvery hair, photophobia, horizontal and rotatory nystagmus and hepatosplenomegaly. Materials and Methods: The clinico-hematological profile of a series of 5 cases of CHS encountered at JIPMER Hospital with diagnostic work-up done in the Department of Pathology over the last 6 years is presented. The diagnostic work-up included complete hemogram with peripheral smear, bone marrow examination, skin and liver biopsies. Results: The age of the patients ranged from 5 months to 3 years. All patients had silvery hair and partial albinism and presented with fever and recurrent chest infection. Two patients were stable. Three patients were in accelerated phase; of them, 1 patient with associated hemophagocytic syndrome had a rapidly fulminant course. Peripheral blood smear showed anomalously large granules in the leukocytes. Skin biopsy showed sparse, coarse melanin pigment in the epidermis, and liver biopsy done in 2 patients with accelerated phase showed portal lymphohistiocytic aggregates. Conclusions: The diagnostic hallmark of CHS is the occurrence of giant inclusion bodies (granules) in the peripheral leukocyte and their bone marrow precursors. The case series is being presented because of the rarity of CHS and varied spectrum of clinical and hematological presentation.